The impact of certain flavourings and preservatives on the survivability of larvae of nematodes of Ruminantia - O. O. Boyko; V. V. Brygadyrenko (Regulatory Mechanisms in Biosystems, 2018)
Annualy, helminthic diseases are one of the causes of economic losses in agriculture. Ruminantia are most often observed to be infected with nematodes of the gastrointestinal tract, including Strongyloides papillosus and the representatives of the Strongylida order. Identifying factors which could cause a decrease in the level of infection of agricultural animals with helminthiases would allow stock-raising facilities to regularly achieve high quality dairy and meat production in sufficient quantity. On the basis of this study, we determined the impact of flavourings and source materials approved for use in and on foods (isoamyl alcohol, isoamyl acetate, raspberry ketone, trilon B, methylparaben) on the survivability of larvae of Strongyloides papillosus and Haemonchus contortus, parasitic nematodes of Ruminantia animals. Among these substances, the lowest efficiency against the nematode larvae was found in isoamyl alcohol, isoamyl acetate and trilon B. A stronger effect was caused by methylparaben (for L3 S. papillosus LD50 = 0.67 ± 0.04%, L1 and L2 S. papillosus – LD50 = 0.0038 ± 0.0008%, L3 H. contortus – LD50 = 0.89 ± 0.15%). Minimum efficient dosage of the solutions was 10 g/l. Significant antihelminthic properties were manifested by raspberry ketone (for L3 S. papillosus LD50 = 1.00 ± 0.72%, L1 and L2 S. papillosus – LD50 = 0.07 ± 0.06%, L3 H. contortus – LD50 = 0.39 ± 0.26%). The results show that there is considerable potential for further studies on the antiparasitic properties of these substances against nematodes in the conditions of farming enterprises and agricultural complexes.